The Influence of Environmental Social Governance (ESG), Profitability, and Capital Structure on Firm Value in IDX ESG Leaders (2020-2023) - Safitri, Ranisa Nur; Paramita, Veronika Santi (Sinergi International Journal of Economics, 2025)
This research examines the firm value on the IDX ESG Leaders index, launched in 2020, and reflects businesses prioritizing ESG principles in their operations. The launch of the index comes amid global economic challenges due to the COVID-19 pandemic, making it relevant to explore how companies can maintain value in volatile markets. The value of IDX ESG Leaders companies declined during 2020-2023. The factors causing the drop in valuation for IDX ESG Leader are allegedly ESG, profitability, and capital structure. With increasing attention to sustainability and social responsibility, ESG is becoming essential in investment decisions. A quantitative strategy based on descriptive causality analysis is used in this study. The data utilized in this study is panel data sourced from secondary materials. The research focuses on companies listed on the IDX ESG Leaders index from 2020 to 2023, encompassing 49 companies. A purposive sampling technique was employed to select a sample of 13 companies. Data analysis was conducted using panel data regression. The findings indicate that ESG has a negative impact on firm value, while profitability positively influences firm value. Additionally, capital structure does not significantly affect firm value. Collectively, ESG, profitability, and capital structure do influence firm value. The study concludes that companies should reconsider their strategies in managing ESG, profitability, and capital structure to enhance their value in the eyes of investors, particularly in an increasingly competitive market.